Governing the police: experience in six democracies - Bayley, David H. (Transaction Publishers, 2016)
Acknowledgements -- A democratic dilemma -- Contexts -- When things go wrong -- History and research -- Setting and systems -- The practice of police governance -- Governing at the cutting edge -- Advice about managing -- Rethinking police governance -- Why governance fails -- The changing contexts of governance -- Improving police governance -- Index